Cover Feature: Heterologous Expression of an Unusual Ketosynthase, SxtA, Leads to Production of Saxitoxin Intermediates in Escherichia coli (5/2021). (15th February 2021) - Soeriyadi, Angela H.; Mazmouz, Rabia; Pickford, Russell; Al‐Sinawi, Bakir; Kellmann, Ralf; Pearson, Leanne A.; Neilan, Brett A.
Abstract : Saxitoxins are neurotoxic alkaloids produced by cyanobacteria and dinoflagellates. Due to their antagonism of voltage‐gated sodium channels, they are desirable candidates for drug development as anaesthetics and muscle relaxants. We describe the heterologous expression and biochemical characterization of the first enzyme in the saxitoxin pathway, SxtA, in E. coli . This unusual polyketide synthase‐like enzyme is able to condense multiple acid‐CoA substrates with arginine and could potentially be exploited for the production of novel compounds of biomedical value. More information can be found in the communication by R. Kellmann, B. Neilan et al. Credits: Bloom photo courtesy of Dr. Nick Crosbie, Melbourne Water. Syringe image by Jupiter Images (sourced through Canva Pro).